2021
DOI: 10.1186/s12871-021-01268-y
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Intraoperative driving pressure with postoperative pulmonary complications in open versus closed abdominal surgery patients – a posthoc propensity score–weighted cohort analysis of the LAS VEGAS study

Abstract: Background It is uncertain whether the association of the intraoperative driving pressure (ΔP) with postoperative pulmonary complications (PPCs) depends on the surgical approach during abdominal surgery. Our primary objective was to determine and compare the association of time–weighted average ΔP (ΔPTW) with PPCs. We also tested the association of ΔPTW with intraoperative adverse events. Methods Posthoc retrospective propensity score–weighted coho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
10
2
Order By: Relevance
“…Compared to other cohorts of abdominal surgery patients, our patient cohort had similar baseline characteristics. 4 , 7 The incidence of postoperative pulmonary complications was 35·9%, which was high compared to other cohorts of patients undergoing abdominal surgery, 2 , 7 but was similar to studies in patients with intermediate–high risk for postoperative pulmonary complications following the ARISCAT classification. 19 , 20 Multiple studies on intraoperative driving pressure have reported similar driving pressure values, 5 , 8 , 24 even in open abdominal surgery.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Compared to other cohorts of abdominal surgery patients, our patient cohort had similar baseline characteristics. 4 , 7 The incidence of postoperative pulmonary complications was 35·9%, which was high compared to other cohorts of patients undergoing abdominal surgery, 2 , 7 but was similar to studies in patients with intermediate–high risk for postoperative pulmonary complications following the ARISCAT classification. 19 , 20 Multiple studies on intraoperative driving pressure have reported similar driving pressure values, 5 , 8 , 24 even in open abdominal surgery.…”
Section: Discussionsupporting
confidence: 74%
“… 19 , 20 Multiple studies on intraoperative driving pressure have reported similar driving pressure values, 5 , 8 , 24 even in open abdominal surgery. 7 Thus far, the intraoperative mechanical power has been reported in cardiothoracic, thoracic, and non–thoracic surgery patients and was slightly higher to that in our patient cohort, with median mechanical power of approximately 8–9 J/min. 24 , 25 , 26 Comparing the two original studies, dynamic mechanical power in the PROBESE study was higher compared to the PROVHILO study, which could be attributed to a higher body mass index in these patients leading to lower chest wall compliance.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A higher ΔP during abdominal closure surgery is usually considered innocent. However, recent research negates this hypothesis [ 20 ]. This study point to a stronger correlation between ΔP in laparoscopic surgery than in abdominal surgery in the analysis of ΔP and postoperative pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive mechanical ventilation leading to excessive parenchymal deformation in people has been associated with a high incidence of postoperative pulmonary complications (29,30). Therefore, the appropriate setting of intraoperative ventilatory variables seems to play an important role in protecting the lungs from ventilator-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%